RESISTENSI TOKOH UTAMA DALAM NOVEL YUNI KARYA ADE UBAIDIL - Nurlaela Agustin; David Setiadi; Fauziah Suparman (Universitas Negeri Makassar, 2023)
This research aims to show the character and characterization of Yuni and the three men who came to propose to her, as well as the form of resistance of female characters to patriarchal culture, in the novel Yuni by Ade Ubaidil. This research uses the descriptive qualitative research method with descriptive analysis. The data used are quotations related to the depiction of characters and characterization and the form of resistance carried out by the main character in the novel. While the data source used is the novel Yuni by Ade Ubaidil. The results of this study show the resistance carried out by the main character (Yuni) in facing the proposal that came from Iman, Mang Dodi, and Pak Damar. The acts of resistance carried out are closed resistance, shown by the attitude of holding back anger when getting ridiculed, and open resistance, shown by Yuni's attitude when rejecting the proposal from the first man, then when rejecting the proposal from the second man, who wants Yuni to be his second wife, and when Yuni runs away from her marriage to the third man as a form of freedom that Yuni wants to get. Thus, it can be concluded that there is one closed resistance and three open resistances in Ade Ubaidil's novel Yuni.